TINJAUAN HUKUM ISLAM TERHADAP PERMOHONAN IZIN POLIGAMI KARENA KETIDAKMAMPUAN PELAYANAN KEBUTUHAN SEKSUAL - Muh Zuhdi Hamdi Fahmi; Asni; Musyfikah Ilyas (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract The main problem that will be studied in this research is the application for a polygamy permit on the grounds of inability to serve sexual needs (Study Decision Number: 663/Pdt.G/2020/Pa.Mrs.). in deciding on case Number: 663/Pdt.G/2020/Pa.Mrs. then the second sub-problem is how to review Islamic law on the decision Number: 663/Pdt.G/2020/Pa.Mrs. The type of research used is a type of Field Research or field research carried out at the Maros Religious Court. This research is also a qualitative research using a normative juridical approach and other legal approaches. The data sources in this study are sourced from primary data and secondary data, then the data is collected through interview and documentation methods. The results of this study indicate: that the judge's legal considerations in deciding case Number 663/Pdt.G/2020/PA Mrs regarding the granting of a polygamy permit are that the applicant has fulfilled faculative reasons according to the provisions of Article 4 paragraph (2) letter (a) in conjunction with Article 57 letter (a). In addition, the applicant has also fulfilled the cumulative requirements in accordance with the provisions of Article 5 paragraph (1) of Law Number 1 of 1974 concerning marriage in conjunction with Article 55 paragraph (2) and Article 58 of the Compilation of Islamic Law. The judge was of the opinion that the reason for polygamy is because of the inability to serve the husband's sexual needs, and the wife cannot carry out her obligations as a wife. Second, the Panel of Judges in making the decision was also guided by Islamic law, namely QS Al-Nisa/4: 3. And also in accordance with fiqh which reads Avoiding mafsadat must take precedence over attracting benefit. The implication of this research is in handling cases related to polygamy permit applications to be more careful and thorough in deciding a case because in this case it can be a legal loophole for a husband to be free to practice polygamy. For people who want to do polygamy, it is expected to think carefully mature before committing polygamy, because later you will be faced with greater responsibilities. If you feel you are unable to act fairly and are unable to meet the needs of your wives and children, then it is enough to marry only one woman, because this is an unjust act. . Keywords: Polygamy, Judge’s Decision, Islamic Law.